Effects of Sodium–Glucose Cotransporter 2 Inhibitors on Calcium Homeostasis: Where We Stand Now - Alessandro Cuttone; Anastasia Xourafa; Carmela Morace; Vittorio Cannavò; Francesca Maria Bueti; Giuseppe Mandraffino; Giovanni Squadrito; Giorgio Basile; Agostino Gaudio; Antonino Catalano; Giuseppina Tiziana Russo; Federica Bellone (Cells)
Diabetes mellitus has been knowingly associated with increased risk of fractures, so much so that skeletal fragility is considered a complication of diabetes. Determinants of bone fragility in this chronic condition are several, and the diabetes treatment choice could influence bone metabolism. Sodium-glucose cotransporter-2 inhibitors (SGLT2i) have recently expanded the therapeutic armamentarium for type 2 diabetes mellitus (T2D); these antihyperglycemic drugs act by reducing renal glucose reabsorption in the proximal tubule and have a proven cardiorenal benefit. The role of SGLT2i towards phospho-calcium metabolism is still unclear, so we aimed to review the current evidence of the relationship between SGLT2i and calcium and phosphate homeostasis. The PubMed, Scopus, and Web of Knowledge databases were searched to identify original research articles, meta-analyses, and scientific reviews on effects on bone metabolism in T2D patients treated with SGLT2i. Emerging data indicate that SGLT2i may lead to a rise of bone turnover markers, promoting a lower skeletal bone density and an increased fracture risk on murine models, but in real-world studies, results are controversial. Therefore, more clinical trials are needed to further clarify this topic, and the effects of SGLT2i on calcium homeostasis remain to date poorly understood.